Limb amputation secondary to pseudoamniotic band syndrome after selective fetoscopic laser photocoagulation: case report - Cunha, Soraia S.; Coutada, Rosália S.; Neiva, Ana R.; Ribeiro, Domingos C. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Pseudoamniotic band syndrome (PABS) is a rare iatrogenic complication that occurs after invasive procedures in monochorionic twins for treatment of twin-twin transfusion syndrome (TTTS). Selective fetoscopic laser photocoagulation (SFLP) is a commonly performed procedure for the treatment of severe TTTS that may lead to complications such as preterm labor, preterm rupture of membranes, cerebral lesions and fetal death. PABS has been reported to occur in up to 3% of cases of TTTS treated with laser, leading to limb abnormalities. There are no identifiable risk factors and antenatal detection of PABS is rare, but possible. Thus, obstetricians should be aware of this possibility in pregnancies treated by laser therapy for TTTS. The authors report a case of a monochorionic biamniotic twin pregnancy submitted to SFLP for TTTS at 19 weeks of gestation with postnatal diagnosis of PABS, presenting with amputation of a fetal limb.